2023
DOI: 10.3389/fgene.2022.934883
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oncogenes and tumor-suppressor genes with hepatocellular carcinoma: A comprehensive analysis based on TCGA and GEO datasets

Abstract: Aim: Existing targeted therapies for hepatocellular carcinoma (HCC) are resistant and have limitations. It is crucial to find new HCC-related target genes.Methods: RNA-sequencing data of HCC were gathered from The Cancer Genome Atlas and Gene Expression Omnibus datasets. Initially, differentially expressed genes between normal and tumor tissues were identified from four Gene Expression Omnibus datasets, GSE36376, GSE102079, GSE54236, and GSE45267. GO terms and KEGG pathway enrichment analyses were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Through consulting the literature , we were particularly interested in PBK, which is overexpressed in several human malignancies 20–24 . By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through consulting the literature , we were particularly interested in PBK, which is overexpressed in several human malignancies 20–24 . By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5.…”
Section: Resultsmentioning
confidence: 99%
“…Through consulting the literature, we were particularly interested in PBK, which is overexpressed in several human malignancies. [20][21][22][23][24] By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5. To further verify that CDK5 phosphorylates PBK-T9, HEK293 cells were transfected with GFP-CDK5 and FLAG-PBK.…”
Section: Phosphorylation Of Pbk At Thr9 By Cdk5 Promotes Cell Prolife...mentioning
confidence: 99%
“…Moreover, FBP1 appears to be a tumor suppressor in HCC progression though negatively regulating the Warburg effect 39 . In addition, studies have demonstrated that the expression of solute carrier family 22 member 1 (SLC22A1), alcohol dehydrogenase 4 (ADH4), solute carrier family 10 member 1 (SLC10A1), and coagulation factor IX (F9) was related to the progression and survival of HCC 6,[40][41][42] . However, there is no reference regarding the integration of these genes for the prognosis of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%